THE ROLE OF PAI TEACHERS IN FORMING STUDENTS' RELIGIOUS CHARACTER AT MTS MA'ARIF KERTEK WONOSOBO - Khalimatus Sakdiyah; Ahmad Khoiri; Fatkhurrohman (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in shaping the religious character of students at MTs Ma'arif Kertek, Wonosobo, the supporting and inhibiting factors that influence this, and the results of student religious character formation. This study uses a qualitative approach with field research. Data were obtained through interviews, observations, and documentation involving Islamic Religious Education teachers, principals, and students. Data were analyzed through data reduction, data presentation, and conclusions drawn using source triangulation for validity. The results indicate that Islamic Religious Education teachers act as educators, mentors, motivators, and role models through ongoing learning, religious practices, guidance, motivation, and role models. The success of religious character formation is supported by the school's religious culture, the involvement of the entire school community, student awareness, and the support of family and peers. However, the influence of social media, social environment, and lack of parental supervision remain obstacles. These roles contribute to the development of students' religious character, demonstrated through devotion to worship, discipline, responsibility, honesty, and courtesy in daily life. Thus, the formation of students' religious character occurs through a continuous process of habituation and mentoring within the school environment.